ANALISIS KANDUNGAN GIZI DAN UJI HEDONIC PADA ABON TULANG IKAN BANDENG - Kasmawati Kasmawati; Yusya Renilda; Zulkifli Zulkifli; Andi Ade Ula Saswini; Andi Zakiah Safitri; Krisno Bimantoro (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Milkfish products without thorns are processed that separate bones from fish meat so that barbed milkfish products are produced (BATARI). Fish thorn waste has not been utilized optimally and has the potential to pollute the environment, even though this waste can be used as shredded fish with high economic value. Shredded products will be received by the public if there is nutritional value information contained in shredded products. This study aims to determine the nutritional content (Proximate) and the percentage of panelists' level of preference for milkfish bone shredded products (hedonic). This research was carried out on March 2 – June 23, 2022, at the UMI Entrepreneurship Laboratory Laboratory. And proximate analysis of fats, proteins and at the Makassar Health Laboratory Center. The results of the shredded proximate test study based on bone type, the highest fat content was shredded fine bone (A) of 18.78%, followed by Hard bone (B) of 11.89% and the lowest in tu lang mix (C) of 9.83%. The highest protein content was found in shredded fine bone (A) of 29.56%, followed by mix bone (C) of 23.97% and the lowest in Hard Bone (B) of 14.8%. The highest calcium content value was found in shredded Hard Bone (B) at 20374.97 ug, followed by mixed bone (C) of 12754.52 ug and the lowest shredded fine bone (A) of 1384.93 ug. Organoleptic Test Results with Appearance Parameters, Panelists chose shredded A with a score of 71.4, followed by Shredded sample B (28.6%). and shredded sample C (42.9%). the level of preference for aroma in shredded B (57.1%) in shredded A (37.5%), and C ( ). Taste in shredded B (57.1%) in shredded A (37.5%), and (C). and texture in shredded B (57.1%) in shredded A (37.5%), and C conclusion The fat, protein and calcium content meet the quality requirements of shredded fish according to SNI. The level of consumer acceptance of color is more dominant in shredded soft bones while the smell, taste and texture are preferred in shredded hard bones